2017
DOI: 10.5539/jfr.v6n5p117
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality and Safety of Winged Termites (Macrotermes bellicosus) Enriched Locally Formulated Complementary Foods

Abstract: Addition of edible insects to local staples used as complementary foods can improve their nutrient content. Nutritional quality and safety of Macrotermes bellicosus enriched boiled rice (BR) and yam (BY) complementary foods (CFs) was assessed using rats. Macrotermes bellicosus (MB) were collected, dried, and refrigerated at -4 o C. Ground MB was added to BR and BY in ratios 10.0%, 15.0%, 20.0% (w/w) to give BR 1 , BY 1 ; BR 2 , BY 2 , and BR 3 , BY 3 respectively. Nutrient content of MB, BY, BR and MB-enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…The presence of variation in the quantity of minerals between the studied insect species could be linked to feed, geographical origins, and anatomical structure of insects [9,16] and the variation can even occur within the same species [12]. These results are supported by the ndings discovered by Adepoju and Ajayi [24] Phenolic compounds are secondary metabolites characterised by the presence of one or more aromatic rings possessing at least one hydroxyl group attached to the aromatic structure [32]. Over decades, it has been discovered that insects can synthesise phenolic compounds in their bodies through the sclerotization process [14].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The presence of variation in the quantity of minerals between the studied insect species could be linked to feed, geographical origins, and anatomical structure of insects [9,16] and the variation can even occur within the same species [12]. These results are supported by the ndings discovered by Adepoju and Ajayi [24] Phenolic compounds are secondary metabolites characterised by the presence of one or more aromatic rings possessing at least one hydroxyl group attached to the aromatic structure [32]. Over decades, it has been discovered that insects can synthesise phenolic compounds in their bodies through the sclerotization process [14].…”
Section: Discussionsupporting
confidence: 53%
“…This suggest that the addition of the studied insects to food or feed could bring about a signi cant increase in essential minerals in the formulated diets. Furthermore, it was shown that the addition of M. subhylanus to formulated complementary food had shown a linear increase in minerals with an increase in the level of inclusion of M. bellicosus [24]. However, Zn content observed in the present study exceeded the maximum limits of the elements in food as recommended by the World Health Organisation (WHO) and the Food and Agriculture Organisation (FAO) [25].…”
Section: Discussioncontrasting
confidence: 50%
“…However, termites and caterpillars consumed in Africa have been found to contain high zinc levels. For example, Adepoju and Ajayi (2016) , Kinyuru et al (2013) , Madibela et al (2007), Mbah and Elekima (2010) , Siulapwa et al (2012) reported that zinc content of termite and caterpillar ranged from 8-16.9 mg/100 g and 8-14 mg/100 g respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The mice experimental diets were formulated to obtain a 10 % protein level and blended with the basal diet, which is presented in Table 2 ( Adejuwon et al., 2021 ; Adeoti et al., 2018 ; Adepoju and Ajayi, 2016 ; Osundahunsi and Aworh, 2003 ). The composition of the experimental food treatments was calculated using Eq.…”
Section: Methodsmentioning
confidence: 99%